Pengaruh Terapi Mewarnai Gambar Terhadap Kecemasan Anak Usia Pra Sekolah - Molintao, Winarsi; Legi, Julita; Adrian, Ivilia (Yayasan Syalom Cipta Sumikolah, 2025)
Every child who is hospitalized will experience feelings of insecurity such as unfamiliar surroundings, separation from parents, lack of information, loss of freedom and independence. Even though the child is sick, the need to play remains. The purpose of this study was to determine the effect of coloring therapy on the anxiety of preschool children in the upper Edelweys room of Bhayangkara Hospital Level III Manado. This type of research uses a